BERPIKIR KREATIF DALAM MEMECAHKAN MASALAH SUBPOKOK BAHASAN SEGITIGA DAN SEGIEMPAT BERDASARKAN ADVERSITY QUOTIENT (AQ) SISWA KELAS VII E SMP NURIS JEMBER - Ra’is, Amin; Hobri, H; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2018)
Abstract. This study aim to knows the creative thinking in solving the problem of sub-topic of triangle and quadrilateral based on adversity quotient (AQ) of class VII E Junior High School at Nuris, Jember. Data collection methods used in this study are questionnaires, tests and interviews. The instruments used are the Adversity Response Profile (ARP) questionnaire, creative thinking ability test in the form of open matter of triangle and quadrilateral material and interview. Of the population of 24 students VII class E was taken as many as 3 students is students who have high AQ value (climber), students who have AQ value being (camper), and students who have low AQ (quitter). That the climber students in the research more precisely have the creative level according to the transition category from camper to climber, camper students in this study according to the camper student category, but in this research quitter students exceed the category of quitter students, more precisely quitter students in research creative according to the transition category from quitter. Keywords: Creative thinking, problem solving, adversity quotient.